The impact of the COVID-19 pandemic on public trust in science - Alain Abi-Rizk (PLoS ONE, 2025)
Public trust in science plays a critical role in shaping attitudes toward health policies, technological advancements, and societal progress. The COVID-19 pandemic profoundly influenced science communication, governmental policies, and public perceptions of scientific credibility. This study examines shifts in trust in science before and after the pandemic using survey data from 10,000 respondents across multiple demographic groups. Results indicate that respondnatds from North America and Europe Experienced an increase in trust where as Africa and South America Witnessed a decline in trust. Males exhibited a greater decline in trust than females (p = 0.038), and undergraduate degree holders showed the largest decrease (p = 0.001). Notably, individuals who relied on independent researchers for scientific information exhibited a slight increase in trust, whereas those who consumed traditional media experienced the largest decline (p < 0.001). These findings highlight the complex dynamics of science trust and the importance of targeted science communication strategies to mitigate erosion in confidence.